Low molecular weight heparin thromboprophylaxis or no treatment following cesarean delivery: A pilot randomized controlled trial - Bruno, Ann; Allshouse, Amanda; Branch, D. Ware; Silver, Robert M; Metz, Torri (American Journal of Perinatology)
Objective: To evaluate the feasibility of randomizing patients to low molecular weight heparin (LMWH) versus no pharmacologic prophylaxis following cesarean delivery (CD). Study Design: Single-center, open-label pilot randomized controlled trial of individuals aged 18+ undergoing CD from November 2023 through June 2024. Those with a contraindication to anticoagulation, a plan for therapeutic anticoagulation, known renal dysfunction, or considered at highest risk for postpartum venous thromboembolism (i.e., high risk thrombophilia, personal history of thromboembolism) were excluded. Eligible and enrolled individuals were randomized in a 1:1 ratio utilizing block randomization with randomly varying block sizes to weight-based LMWH for 14 days or no pharmacologic thromboprophylaxis. The primary outcome was feasibility, defined as ≥35% enrollment of eligible individuals and retention of ≥85% of enrolled individuals. Secondary feasibility outcomes included the number of eligible patients per month, approach rate, enrollment rate, and retention rate. Baseline characteristics were compared between those approached and enrolled and those not enrolled. The proportion meeting each of the outcomes was reported with 95% confidence intervals (CI). Results: Over the six-month study period, 694 patients were screened and found eligible for an average of 106 eligible patients per month. There were 611 patients approached (88%, 95% CI 85.6-90.5%), of which 64 enrolled (10.5%, 95% CI 8-12.9%) and 61 participants were retained through all study procedures (n=61/64, 95.3%, 95% CI 90-100%). Thus, the overall primary outcome feasibility parameters were not met. Among the 64 individuals enrolled, the mean age was 31.0 years, and the majority were non-Hispanic White (56%). Baseline characteristics were similar between those who were approached and enrolled compared with those not enrolled. Conclusion: In this pilot trial, individual patient randomization to LMWH or no pharmacologic thromboprophylaxis after CD was not feasible due to low enrollment rates. Future trials addressing postpartum thromboembolism prevention should consider alternative study designs.